Інформаційна система "Віртуальна хімія" для учнів з особливими освітніми потребами - Козубенко, Андрій Віталійович; Kozubenko, Andrii Vitaliiovych (Національний університет "Львівська політехніка", 2024)
У зв’язку зі зростанням числа учнів у класах, орієнтованих на задоволення інклюзивних вимог (збільшення більш ніж утричі за останні п’ять років), та функціонуванням понад 660 інклюзивно-ресурсних центрів навіть за умов воєнного стану, забезпечення якісного інклюзивного навчання вимагає нових цифрових інструментів [1][2]. Законодавча база (ратифікація Конвенції ООН 2009 р. і Закон України «Про освіту» 2017 р.) гарантує право дітей з особливими освітніми потребами (ООП) на навчання в загальноосвітніх школах із необхідною корекційно-розвитковою та психолого-педагогічною підтримкою [3]. Об’єкт дослідження – процеси навчання шкільного курсу хімії дітей з ООП із застосуванням технологій віртуальної реальності. Предмет дослідження – методи й засоби розробки інформаційної системи «Віртуальна хімія», що використовує «VR»-технології для адаптації навчального середовища до індивідуальних потреб учнів з ООП. Мета дослідження – створити інтерактивну інформаційну систему «Віртуальна хімія» для полегшення, покращення та уможливлення вивчення базового курсу шкільної хімії учнями з ООП за допомогою «VR»-лабораторії та бекенд-аналітики. Результати дослідження – проведено огляд стану інклюзивної освіти в Україні й світових практик «VR»-навчання, виявлено прогалини в доступних рішеннях [4]. Сформульовано цілі та вимоги до «Віртуальної хімії», побудовано дерево цілей, функціональні діаграми, ієрархію задач і «ER»-модель бази даних для задоволення потреб учнів з ООП. Підтверджено, що поєднання інклюзивних методик і «VR»-технологій відкриває нові можливості для вивчення шкільної хімії учнями з ООП, зокрема через інтерактивне моделювання безпечних експериментів і розвиток просторового мислення [5]. Контрольний приклад продемонстрував повну відповідність реалізації цілей і завдань: від побудови і моделювання реакцій, візуалізації результатів у динамічний та інтерактивний способи й реалізації повноцінної інформаційної з метою імплементації функціоналу, необхідного не лише для симуляції реакцій, а й збереження інформації щодо учнів та вчителів в інклюзивних класах.

Over the past five years, the number of students in inclusive-oriented classes in Ukraine has more than tripled, and over 660 inclusive-resource centres continue to operate even under martial law, providing essential corrective and psycho-pedagogical support [1][2]. The ratification of the UN Convention on the Rights of Persons with Disabilities in 2009 and the 2017 Law of Ukraine “On Education” guarantee the right of students with special educational needs (SEN) to attend mainstream schools with appropriate support services [3]. Study Object – the processes of teaching the school-level chemistry curriculum to students with SEN using virtual reality (VR) technologies. Scope of Research – the methods and tools for designing and developing the “Virtual Chemistry” information system, which employs VR to adapt the learning environment to the individual needs of students with SEN. Goal of Research – to create an interactive information system – “Virtual Chemistry” – that facilitates and enhances the learning of core school chemistry by students with SEN through a VR laboratory and backend analytics. Research Methods and Design – a comprehensive review of the state of inclusive education in Ukraine and global VR-based learning practices revealed significant gaps in solutions tailored for students with SEN [4]. Based on this, project objectives and requirements were defined, and a system model was developed using a goal tree, functional diagrams, task hierarchy, and an entity-relationship database schema to ensure alignment with the needs of the target audience. Research results – A review of the state of inclusive education in Ukraine and world-wide VR-learning practices was carried out, and gaps in the available solutions were identified [4]. The goals and requirements for “Virtual Chemistry” were formulated; a goal tree, functional diagrams, a task hierarchy, and an ER-model of the database were built to meet the needs of students with special educational needs. It was confirmed that the combination of inclusive methods and VR-technologies opens new possibilities for teaching school-level chemistry to students with special educational needs, in particular through interactive simulation of safe experiments and the development of spatial thinking [5]. The control example demonstrated full compliance of the implementation with the stated objectives and tasks: from constructing and simulating reactions, to dynamic and interactive visualization of results, and the complete implementation of informational functionality necessary not only for simulating reactions but also for storing information about students and teachers in inclusive classrooms.
Information system "Virtual Chemistry" for students with special educational needs
Keywords: 6.126.00.01; – інклюзивна освіта; віртуальна реальність; особливі освітні потреби; моделювання хімічних реакцій; inclusive education; virtual reality; special educational needs; chemical reaction simulation